The Role of the IKM Gallery as a Container for SME Activities in the Industrial Field at the Department ff Cooperative, Small, Medium Business, Trade, and Industrial Cirebon City - Riri Fitriah Oktafian; Achmad Otong Bustomi (Cirebon International Journal of Economics and Business, 2023)
The development of Small and Medium Industries (IKM) in an area is one of the bridges to encourage regional economic growth. The development of IKM in Cirebon City has increased a lot from year to year, although there are percentages that show a decrease. However, the current condition, the existence and location of IKM is still very rarely known by the public due to the lack of information about the IKM itself. This study used a descriptive research method design using a qualitative approach. The purpose of this article is to explain the role of the IKM GALLERY in the industrial sector at the Office of Cooperatives for Small and Medium Enterprises of Trade and Industry in the City of Cirebon. The results of this study indicate that the IKM GALLERY in the city of Cirebon in general has been running well and is very useful for the business development of IKM actors, but in terms of applicability the results achieved have not fully achieved optimal results. In addition, the IKM GALLERY is one of the facilitators in promotion and marketing which is under the auspices of the government agency, the Department of Cooperatives for Small and Medium Enterprises of Trade and Industry in the City of Cirebon.